Research report of Mongolia, April-May, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Mentions of photographs
Keywords: Arid regions; Livestock; Prices; Weather; Household Income; Lockdown; Mongolia; COVID-19 Pandemic